2020
DOI: 10.3390/healthcare8040490
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Childhood Trauma, Eating Disorders, and Sleep Quality among Registered Hospital Nurses in South Korea

Abstract: This cross-sectional study examined the relationship between childhood trauma, eating disorders, and sleep quality among registered hospital nurses in South Korea. Self-report questionnaires were answered by 279 nurses from six general hospitals. Factors affecting sleep quality were analyzed with a linear regression analysis. The factors that influenced sleep quality included age, alcohol consumption, chronic disease, BMI, and emotional abuse in childhood trauma. Hospital nurses need to increase their sleep he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…The results showed that ACEs significantly affected the sleep quality of people with drug addiction and non-addicts. Adults who have experienced ACEs tend to have worse sleep quality (Jung & Oh, 2020). Abuse in childhood may lead to a series of long-term sleep changes and produce sleep disorders, which emerge in the early stages of life and extend into adulthood (Lewin et al, 2019).…”
Section: Aces Affected the Sleep Quality Of People With Drug Addictio...mentioning
confidence: 99%
“…The results showed that ACEs significantly affected the sleep quality of people with drug addiction and non-addicts. Adults who have experienced ACEs tend to have worse sleep quality (Jung & Oh, 2020). Abuse in childhood may lead to a series of long-term sleep changes and produce sleep disorders, which emerge in the early stages of life and extend into adulthood (Lewin et al, 2019).…”
Section: Aces Affected the Sleep Quality Of People With Drug Addictio...mentioning
confidence: 99%
“…It not only improves physical health but also affects sleep quality, which is important in maintaining a long-lasting healthy life [ 8 , 19 ]. Previous studies reported that physical activity showed the lowest score of occurrences among health-promoting behaviors [ 20 ] and that working women and elderly women have low sleep quality [ 21 , 22 ]. However, there are very few studies that have examined the sleep quality and physical activity among middle-aged women in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…It not only improves physical health but also affects sleep quality, which is important in maintaining a long-lasting healthy life. 7,12 In previous studies, it was reported that physical activity showed the lowest score of occurrences among health-promoting behaviors 13 and that working women and elderly women have low sleep quality, 14,15 but there are very few studies examining the sleep quality and physical activity among middle-aged women in South Korea. Physical activity is known to maintain women's health, and physical inactivity is an important factor in various chronic diseases such as obesity, diabetes, and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%